Upaya Upt Ltk Disnaker Kota Cirebon Dalam Mengurangi Pengangguran Melalui Program Pelatihan Kerja Berbasis Kompetensi: Indonesia - Muhit, Ryan Abdul (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
Workers who have more potential in terms of quality can encourage the economic development of a country. One of the government's roles in overcoming unemployment is through a job training program held by the Cirebon City Manpower Service as a Technical Implementation Unit for Manpower Training. This study uses a qualitative approach. The result of this research is that the implementation of labor training at the Manpower Training UPT of the Cirebon City Manpower Office is in accordance with the mandate of the Government and legislation. Then, the effort of the UPT LTK of the Cirebon City Manpower Service in reducing unemployment through competency-based job training programs is (1) job training that emphasizes skills without ignoring theory so that later workers can become independent (create jobs) and directly practice in the world of work, (2) by looking at the qualifications of the workforce themselves when registering for participation in the workforce training program, and (3) adding partners with companies to support graduates who take part in the workforce training program.